Baim Wong Digital Footprint Formation of Online Identity in the Social Media Era : Jejak Digital Baim Wong Pembentukan Identitas Daring di Era Media Sosial - Lestari, Tri Yunanda Ayu (Universitas Muhammadiyah Sidoarjo, 2025)
In the era of rapidly growing social media, public figures like Baim Wong face complex challenges in shaping and managing their online identities. This article analyzes in depth how Baim Wong, as an Indonesian celebrity, builds his online identity on various digital platforms, such as Instagram and YouTube, and how he manages the phenomenon of